How the Robin got its red breast : a legend of the Sechelt People - Sechelt Nation; Craigan, Charlie, ill. (Gibsons, BC : Nightwood Editions, 1993)
These traditional teaching legends come straight from the oral traditions of the Sechelt Nation. Simple enough to be understood by young children, yet compelling enough for adults, they are gentle, beautifully presented cautionary tales. You'll want to read them again and again - and you'll learn a few words of the Shishalh language while you're at it. Charlie Craigan is a young Sechelt artist who works in a tiny studio set up in his bedroom. He studied traditional wood carving with Sechelt Nation carvers, but learned to draw and paint by studying books.
Principal illustrations, based on traditional Sechelt designs, copyright 1993 by Charles Craigan.
Last page a summary of Sechelt history. Book produced, written and copyright to Sechelt Nation.
About Charlie Craigan. Charles Joseph (Charlie) Craigan, who illustrated this story, was born in Sechelt BC in 1969. His natural artisitc talent began showing itself while he was still a Grade Five student at Sechelt Elementary and was further developed while working with carvers Arnold Jones and Jamie Jeffries. Charlie is a member of the Sechelt Indian Band and lives on the band lands in Sechelt. Charlie dedicates the illustrations in this book to the elders of the Sechelt nation.
All Juvenile
Keywords: Sechelt -- Legends -- Children's literature; First Nations -- Legends -- Robins; Canadian literature (English) -- First Nations authors; First Nations -- Legends -- Robins; First Nations -- Legends -- British Columbia; First Nations -- Children's literature